PERTANGGUNGJAWABAN HUKUM PIDANA RUMAH SAKIT SEBAGAI KORPORASI PELAYANAN KESEHATAN - Febi Irianto (SOL JUSTICIA, 2021)
This study discusses the Criminal Legal Liability of Hospitals as Health Service Corporations. The purpose of this study was to find out how the hospital's criminal liability is to patients as consumers of health services. The research method used is normative (doctrinal legal research). Juridically doctrinally, the hospital is responsible for the negligence of health workers with the doctrine of respondent superior, and the hospital is responsible for the quality of care (duty to care); and theoretically juridical, the hospital as a corporation, the principles of vicarious liability, hospital liability, and corporate liability apply, so that the hospital can be held accountable for mistakes made by health workers who work in a subordinate position (employee). Hospitals as legal entities, are responsible for medical actions taken by their doctors, namely ethical and legal responsibilities. Ethical responsibilities generally include professional disciplinary responsibilities, while legal responsibilities include criminal, civil, and administrative legal responsibilities.